The impact of storage conditions on platelets in platelet-rich plasma (PRP) and platelet concentrate (PC) - Lucky Sriwastwa; Khushboo Shrivastava; Ashish Ranjan; C.P. Jaiswal; Tirumala Kanakadurga Sripati (Student's Journal of Health Research Africa, 2023)
Introduction: The ultimate aim of blood transfusion services is to give recipients whole blood and blood components that are secure, efficient, and potent. Control, assurance, and audit of quality are the foundational elements of quality. Product standards are developed and accurately met through the process of quality control.